Improvement of lipids and reduction of oxidative stress with octacosanol after taekwondo training - Lee, S.-H.; Scott, S. D.; Pekas, E. J.; Lee, J.-G.; Park, S. -Y. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Athletes in combat sports undergo rapid changes in body weight prior to competition in order to gain a size advantage over their opponent. However, these large weight changes with concomitant high-intensity exercise training create poor lipid profiles and high levels of oxidative stress, which can be detrimental to health and sport performance. Therefore, the purpose of this study was to investigate the ability of the nutritional supplement octacosanol to combat the physiological detriments that occur in taekwondo players during rapid weight loss with high-intensity exercise training. Methods: A total of 26 male taekwondo players were randomly divided into 2 groups: An experimental group performed a 5% weight-loss and taekwondo training program with 40-mg octacosanol intake (OCT; n = 13) for 6 d, and a control group performed the same weight-loss and taekwondo training program with a placebo (CON; n = 13). Results: There were significant (P < .05) group × time interactions for low-density lipoprotein and triglycerides, which significantly decreased ( 18 [5] mg/dL and Delta 80 [7] mg/dL, respectively), and high-density lipoprotein, which significantly increased ( 10 [7] mg/dL), in the OCT group compared with the CON group. There were also significant (P < .05) group × time interactions for superoxide dismutase (SOD), glutathione peroxidase (GPx), and malondialdehyde (MDA), with SOD increasing (Delta 226 [121] U/gHb) in the OCT group, while GPx decreased ( 20 [13] U/gHb) and MDA increased (Delta 72 [0.04] nmol/mL) in the CON group. Conclusion: These results suggest that octacosanol may be a beneficial supplement to protect against the poor cholesterol levels and oxidative stress that occurs during taekwondo training.